Embracing Scientific Debate in Brain Metabolism - Andersen, Jens V.; Aldana, Blanca I.; Bak, Lasse K.; Behar, Kevin L.; Borges, Karin; Carruthers, Anthony; Cumming, Paul; Derouiche, Amin; Díaz-García, Carlos M.; Drew, Kelly L.; Duarte, João M.N. ; 0000-0001-5984-1574; Ferreira, Gustavo C.; et al. (Journal of Neurochemistry, 2025)
Brain metabolism is a fascinating and exciting research topic. Many new metabolic features of the brain continue to be unveiled and much remains to be discovered. To truly enable scientific progress, it is imperative that discoveries and theories are continually challenged through scholarly discussion. Here we address an earlier editorial by Bolaños et al. 2025 to underline the importance of embracing and respectfully engaging in scientific debate. (Figure presented.).
Keywords: metabolic shuttles; metabolism; neuron–glia interactions